2021
DOI: 10.3390/agriculture11080793
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Rice Husk Biochar and Lime Increases Phosphorus Availability and Maize Yield in an Acidic Soil

Abstract: Biochar, a pyrogenic carbon, has been receiving incremental attention for potential contribution to soil health, agricultural productivity enhancement while mitigating climate change by sequestering carbon and reducing greenhouse gas (GHG) emissions. However, it is not well-known to us how far rice husk biochar (RHB) application rates could increase phosphorus (P) bioavailability and plant performance when co-applied with P and lime. Here, we present data of a pot experiment consisting of eleven treatments to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…According to [ 40 ], the photosynthetic rate was analyzed in five selected plants per plot in week 13 after the start of the experiment using a portable photosynthesis device (Li-6400XT, NE, USA). The chlorophyll index was determined by a 508 SPAD chlorophyll meter and the leaf area was measured with the Delta-T (Divises Ltd., Hatfield, UK).…”
Section: Methodsmentioning
confidence: 99%
“…According to [ 40 ], the photosynthetic rate was analyzed in five selected plants per plot in week 13 after the start of the experiment using a portable photosynthesis device (Li-6400XT, NE, USA). The chlorophyll index was determined by a 508 SPAD chlorophyll meter and the leaf area was measured with the Delta-T (Divises Ltd., Hatfield, UK).…”
Section: Methodsmentioning
confidence: 99%
“…Biochar generally has a neutral or slightly alkaline pH, and its alkalinity increases with the pyrolysis temperature, typically carried out at 300 up to 600 • C, under little or no oxygen conditions [39]. The literature abounds with studies showing that biochar, as a soil additive, has the ability to raise the soil pH (that is, to neutralize its acidity) [40][41][42][43]. It has also been demonstrated that biochar contains many alkaline substances, including calcium carbonate in amounts ranging from 0.5% to 33%, and thus can increase the pH of soils [44].…”
Section: Soil Ph After Biochar Applicationmentioning
confidence: 99%
“…Applying biochar increases available P in the soil and P uptake by plants in acid soils [29]. Combined application of rice husk biochar, P fertilizer, and lime significantly increased soil pH and P availability and decreased Al and Fe toxicity [30]. In this research, the water hyacinth compost used has a humic acid content of around 1.48% and a fulvic acid content of about 0.93%.…”
Section: Changes In the Soil Chemical Properties Under Oxidizing Cond...mentioning
confidence: 80%